COMPILATION OF LEARNER’S DICTIONARY AS A TOOL FOR LEXICOGRAPHIC COMPETENCE OF NON-LINGUISTIC SPECIALTIES STUDENTS - Korol, Larysa (Collection of scientific papers «ΛΌГOΣ», 2023)
Nowadays, the techniques of acquiring and presenting information are being actively introduced into the learning process. Ukraine’s entry into the educational space of Europe updates the objective of increasing the efficiency of foreign language teaching in non-linguistic specialties. The need to develop future professionals’ ability to communicate in English and other foreign languages in the extreme situation caused by the Russian-Ukrainian war is especially urgent. Current challenges, however, necessitate the updating of strategies, methods, and techniques for language learning in higher education.